Edukasi Anak dalam Perspektif Surat Luqman Ayat 12–13 - Iskandar Muda; Jailani Syahputra Siregar; Endi Zunaedy (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
Children's education in Islam is a fundamental aspect that plays a strategic role in shaping the character and morality of the younger generation, directly impacting the development of a civilized and religious society. Surah Luqman verses 12–13 provide essential guidance on core principles of Islamic education rooted in values of monotheism and ethics. This study is motivated by the need for an educational model that integrates spiritual values and addresses current educational challenges. The objective of this study is to examine the concept of children's education as presented in these two verses of the Qur'an. This research adopts a qualitative approach using content analysis. The findings indicate that monotheism (tauhid) serves as the foundational basis for character formation, as emphasized in Luqman’s warning against associating partners with God (shirk). Other key values, such as gratitude and moral behavior, also contribute to building an Islamic character. The contribution of this study lies in enriching Islamic educational literature and providing a conceptual framework for parents and educators to instill noble values from an early age.